FORMING INDIVIDUAL LEARNING TRAJECTORIES IN VISUAL ARTS THROUGH DIGITAL PLATFORMS - Karimova Gulnoza Radjabovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the methodology of forming individual learning trajectories in visual arts using digital platforms. The study focuses on how online tools, learning management systems, and interactive digital resources can support personalized learning, enhance students’ creative competencies, and foster independent artistic development. Digital platforms enable students to progress at their own pace, access diverse instructional materials, and receive feedback tailored to their needs. Integrating these technologies into visual arts education promotes engagement, motivation, and a more effective and individualized learning process.